Varying Dosages of Subcutaneous Unfractionated Heparin and Activated Partial Thromboplastin Time in Hospitalized Antepartum Patients: A Retrospective Cohort Analysis. (12th January 2022) - Elmofty, Dalia H.; Tucker, Andrew; Wuenstel, Andrew M.; Cheng, Paul K.; Fox, Edward; Knoebel, Randall; Liao, Chuanghong; Scavone, Barbara
Abstract : BACKGROUND: Venous thromboembolism (VTE) is a leading cause of maternal morbidity and mortality in the United States. Subcutanous unfractionated heparin (UFH) has been used for decades for VTE prophylaxis and under many obstetric quality of care initiatives, hospitalized antepartum patients now receive doses as high as 10, 000 units every 12 hours. This practice increases the likelihood of UFH administration around the time that epidural labor analgesia is requested or neuraxial analgesia for cesarean delivery is needed. To clarify the effect of UFH on coagulation, we reviewed the care of hospitalized antepartum patients receiving VTE prophylaxis with UFH to determine the incidence of concurrent abnormal activated partial thromboplastin time (aPTT) values and associated risk factors. METHODS: This retrospective cohort study used data from the University of Chicago Pharmacy database to identify hospitalized antepartum patients receiving subcutaneous UFH from June 1, 2016 to July 1, 2019. Our institutional protocol states that all patients hospitalized for antepartum conditions should receive pharmacologic prophylaxis empirically unless contraindicated. For patients receiving UFH, dosing was based on gestational age: 5000 units every 12 hours for first trimester antepartum patients, 7500 units every 12 hours for second trimester patients, and 10, 000 units every 12 hours for patients in the third trimester. As per protocol, aPTT values were obtained 2 hours after the third dose of heparin, and platelet counts after 4 days. Data collection included demographics, comorbidities, heparin doses, aPTT values, platelet counts, creatinine if available, and anesthetic type and complications. Logistic regression was performed to determine the association between elevated aPTT >40 seconds and study variables. RESULTS: Of the 321 antepartum patients who received subcutaneous UFH, 33 (10.3%) had an aPTT >40 seconds, 4 of those 33 patients (12.1%) received 5000 units every 12 hours, 14 (42.2%) received 7500 units every 12 hours, and 15 (45.5%) received 10, 000 units every 12 hours. The likelihood of a patient having aPTT >40 seconds was 2.8% with 5000 units every 12 hours, 18.9% with 7500 units every 12 hours, and 14.6% with 10, 000 units every 12 hours. CONCLUSIONS: Elevated aPTT values are likely with total daily doses of 15, 000 or 20, 000 units subcutaneous UFH in hospitalized antepartum patients.